School-Based Mental Health Services for Racial Minority Children in the United States - Shinwoo Choi; Hyejoon Park; Yeongbin Kim; Ching-Hsuan Lin (International Journal of School Social Work, 2022)
Racial minority children have been an underserved population and are particularly vulnerable due to limited access to community resources, especially mental health services. Schools have been noted as appropriate that environment to deliver services for underserved children (Blewett, Casey, & Call, 2004). However, little is known about the effectiveness of exiting school-based services targeting minority students. Therefore, this study reviewed past research regarding the effects of school-based mental health services (SBMHS) for racial minority children and analyzed the methodological and cultural features. By applying the Levels of Evidence-Based Intervention Effectiveness (LEBIE) scale and the cultural sensitivity criteria, the researchers examined whether existing SBMS were designed with rigor and cultural sensitivity. Our study analyzed the effects of SBMS with child-centered play therapy or resilience-building programs on mental illness of racial minority groups of children, such as increasing social connectedness and decreasing depressive symptoms. Our study findings implied that SBMS should be provided for students of color who have limited access to resources and health care services in their communities. School professionals also need to reach out in multiple contexts to students of color by understanding structural racism and oppression.
Keywords: school-based mental health service; racial minority children; school-based intervention; underserved population